Respiration defects limit serine synthesis required for lung cancer growth and survival - Eduardo Cararo Lopes; Fuqian Shi; Akshada Sawant; Maria Ibrahim; Maria Gomez-Jenkins; Zhixian Hu; Pranav Manchiraju; Vrushank Bhatt; Wenping Wang; Christian S. Hinrichs; Douglas C. Wallace; Xiaoyang Su; et al. (Nature Communications)
Abstract Mitochondrial function supports energy and anabolic metabolism. Pathogenic mitochondrial DNA (mtDNA) mutations impair these processes, causing mitochondrial diseases. Their role in human cancers is less clear; while some cancers harbor high mtDNA mutation burden, others do not. Here we show that a proofreading mutant of DNA polymerase gamma (PolGD256A) increases the mtDNA mutation burden in non-small-cell lung cancer (NSCLC). This mutation promotes the accumulation of defective mitochondria, reduces tumor cell proliferation and viability, and improves cancer survival. In NSCLC, pathogenic mtDNA mutations enhance glycolysis and create a glucose dependency to support mitochondrial energy, but at the expense of a lower NAD+/NADH ratio that hinders de novo serine synthesis. Thus, mitochondrial function in NSCLC is essential for maintaining adequate serine synthesis, which in turn supports the anabolic metabolism and redox homeostasis required for tumor growth, explaining why these cancers preserve functional mtDNA.